The interplay between aerobic metabolism and antipredator performance: vigilance is related to recovery rate after exercise - Killen, Shaun S.; Reid, Donald; Marras, Stefano; Domenici, Paolo (Frontiers in Physiology, 2015)
When attacked by a predator, fish respond with a sudden fast-start motion away from the threat. Although this anaerobically-powered swimming necessitates a recovery phase which is fuelled aerobically, little is known about links between escape performance and aerobic traits such as aerobic scope or recovery time after exhaustive exercise. Slower recovery ability or a reduced aerobic scope could make some individuals less likely to engage in a fast-start response or display reduced performance. Conversely, increased vigilance in some individuals could permit faster responses to an attack but also increase energy demand and prolong recovery after anaerobic exercise. We examined how aerobic scope and the ability to recover from anaerobic exercise relates to differences in fast-start escape performance in juvenile golden grey mullet at different acclimation temperatures. Individuals were acclimated to either 18, 22, or 26oC, then measured for standard and maximal metabolic rates and aerobic scope using intermittent flow respirometry. Anaerobic capacity and the time taken to recover after exercise were also assessed. Each fish was also filmed during a simulated attack to determine response latency, maximum speed and acceleration, and turning rate displayed during the escape response. Across temperatures, individuals with shorter response latencies during a simulated attack are those with the longest recovery time after exhaustive anaerobic exercise. Because a short response latency implies high preparedness to escape, these results highlight the trade-off between the increased vigilance and metabolic demand, which leads to longer recovery times in fast reactors. These results improve our understanding of the intrinsic physiological traits that generate inter-individual variability in escape ability, and emphasise that a full appreciation of trade-offs associated with predator avoidance and energy balance must include energetic costs associated with vigilance and recovery